2007
DOI: 10.1007/s10633-007-9066-9
|View full text |Cite
|
Sign up to set email alerts
|

Flicker assessment of rod and cone function in a model of retinal degeneration

Abstract: Critical flicker frequency (CFF) is the lowest frequency for which a flickering light is indistinguishable from a non-flickering light of the same mean luminance. CFF is related to light intensity, with cone photoreceptors capable of achieving higher CFF than rods. A contemporaneous measure of rod and cone function can facilitate characterization of a retinal degeneration. We used sinusoidal flicker ERG to obtain CFF values, over a wide range of light intensities, in RCS dystrophic (RCS-p(+)) and wild type rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…Cone survival in P23H rats depends on the mutation (Machida et al, 2000) and previous studies have documented cone degeneration from P21 in P23H-1 rats (Machida et al, 2000; Cuenca et al, 2004; Pinilla et al, 2005a; García-Ayuso et al, 2013), but also long term cone survival for P23H-3 rats (Chrysostomou et al, 2009; Lu et al, 2013; Fernández-Sánchez et al, 2015). In the RCS strain, previous electrophysiological and morphological studies have indicated that cone cell death may begin before P30 (Pinilla et al, 2005b; Rubin and Kraft, 2007; Huang et al, 2011). …”
Section: Discussionmentioning
confidence: 94%
“…Cone survival in P23H rats depends on the mutation (Machida et al, 2000) and previous studies have documented cone degeneration from P21 in P23H-1 rats (Machida et al, 2000; Cuenca et al, 2004; Pinilla et al, 2005a; García-Ayuso et al, 2013), but also long term cone survival for P23H-3 rats (Chrysostomou et al, 2009; Lu et al, 2013; Fernández-Sánchez et al, 2015). In the RCS strain, previous electrophysiological and morphological studies have indicated that cone cell death may begin before P30 (Pinilla et al, 2005b; Rubin and Kraft, 2007; Huang et al, 2011). …”
Section: Discussionmentioning
confidence: 94%
“…Humans as well as cats can decode up to ϳ70 Hz of flickering visual stimuli. However, in rats, even though the critical flicker frequency (CFF) of electroretinogram responses could be as high as 50 Hz (Rubin and Kraft, 2007), the CFF of the cells in the visual cortex was found to be ϳ20 Hz (Wells et al, 2001). Evolutional merit of the features found at this synapse may exist for rats, and, as all visual information must pass through the LGN before it reaches the visual cortex, this synapse would be an ideal location for signal filtering optimized for each species.…”
Section: Discussionmentioning
confidence: 99%
“…The normal morphology of P21 RCS rats seen here is consistent with previously reported functional changes in RCS rats. Cone function, evaluated using the amplitude of cone-driven critical fl icker frequency 25 and threshold multiunit responses recorded from the superior colliculus in light-adapted rats, were nearly normal at P21-25 in RCS rats. 8 An implication of this fi nding for therapeutic strategies is that, to achieve preservation of cone function, therapies should be performed prior to the completion of cone development.…”
Section: Discussionmentioning
confidence: 99%